2009
DOI: 10.1021/jf902371j
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection and Differentiation of Alicyclobacillus Species in Fruit Juice Using Hydrophobic Grid Membranes and Attenuated Total Reflectance Infrared Microspectroscopy

Abstract: Pasteurized juices may undergo spoilage during normal shelf life due to Alicyclobacillus spp. Metabolic byproducts during germination of these thermoacidiophilic, endospore-forming bacteria impart off-flavors. The objective was to develop a simple, rapid, and sensitive approach for differentiation of Alicyclobacillus spp. by attenuated total reflectance infrared (ATR-IR) microspectroscopy after isolation onto hydrophobic grid membrane (HGM) filters. Dilutions of four different species of Alicyclobacillus were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…In addition to providing a means of classifying objects, residuals provide valuable information regarding class homogeneity, separation between classes (interclass distance), and the relative strength of any given variable to model the structure of a class or to discriminate between classes (discriminating power). SIMCA's interclass distance (ICD) describes quantitatively the similarity or dissimilarity of the different classes, being generally accepted that samples can be differentiated when ICD >3 (Grasso et al, 2011). The discriminating power of variables may be used to eliminate noise from the data set, such that variables having both low discriminating power and modelling power can be eliminated.…”
Section: Multivariate Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to providing a means of classifying objects, residuals provide valuable information regarding class homogeneity, separation between classes (interclass distance), and the relative strength of any given variable to model the structure of a class or to discriminate between classes (discriminating power). SIMCA's interclass distance (ICD) describes quantitatively the similarity or dissimilarity of the different classes, being generally accepted that samples can be differentiated when ICD >3 (Grasso et al, 2011). The discriminating power of variables may be used to eliminate noise from the data set, such that variables having both low discriminating power and modelling power can be eliminated.…”
Section: Multivariate Data Analysismentioning
confidence: 99%
“…MIR-microspectroscopy has been successfully applied in detecting subtle compositional differences between microorganisms at strain and serovar level (Grasso, Yousef, De Lamo Castellvi, & Rodriguez-Saona, 2011;Prabhakar, Kocaoglu-Vurma, Harper, & Rodriguez-Saona, 2011) and results showed that this technology could provide rapid, simple and reliable screening procedure for the industry.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the bacteria could be classified at species and strain levels by soft independent modeling. The accuracy of the model in correctly predicting Alicyclobacillus reached 100% in blind tests (62).…”
Section: Juicementioning
confidence: 97%
“…Rapid detection of bacteria in the industrial production of juice is important. In 2009, IMS in ATR mode was used to study the rapid detection and differentiation of Alicyclobacillus species in fruit juice (62). The data were analyzed by multivariate analysis.…”
Section: Juicementioning
confidence: 99%
“…Fourier transform infrared microspectrsocpy (FT-IRMS) combined with multivariate data analysis is a well known method for the analysis of chemicals and microorganisms [13,14]. Specifically, attenuated total reflectance infrared microspectroscopy (IRMS) has the potential of detecting subtle compositional differences between samples.…”
Section: Introductionmentioning
confidence: 99%